PENERAPAN METODE THE POWER OF TWO UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI SMPN 1 TURIKALE - Rahman, Marwah Khaerana; Syahid, Akhmad; Sudarmono, Muh Aidil; Bunyamin, Andi; Nengsih, Ratika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is a Classroom Action Research (CAR) aimed at improving students’ learning activeness and learning outcomes through the implementation of the The Power of Two learning method in Islamic Religious Education (PAI) on the topic of Believing in the Holy Books of Allah in class VIII-F at SMPN 1 Turikale Maros. The research subjects consisted of 32 students. The study was conducted in two cycles, each comprising planning, action, observation, and reflection stages. Data were collected through observation and learning achievement tests. The results showed that the implementation of the The Power of Two method improved students’ activeness and learning outcomes. Learning activeness increased from 77% in Cycle I (high category) to approximately 85% in Cycle II (very high category). In addition, learning outcomes also improved, with 87.5% of students achieving the Minimum Mastery Criteria (KKM) in Cycle II, where 68.75% obtained grade A and 18.75% obtained grade B. Therefore, the The Power of Two method proved to be effective in enhancing students’ active participation and learning outcomes. Keywords: The Power of Two, Learning Outcomes, Islamic Education.